A typology of the sources of mental health precarity among migrant workers in India during the COVID-19 lockdown - Mookerjee, Devalina; Roy, Shubhabrata (Frontiers in Communication, 2023)
When urban workplaces shut down for the COVID-19 pandemic lockdown in India, a very large number of migrant workers were forced to reverse-migrate to their largely rural points of origin. This article looks at the mental health implications of the period migrants spent without work, back at the low-resource places from which they had out-migrated, in hopes of a better life. Based on qualitative interviews conducted with reverse migrants during the COVID-19 pandemic lockdown, this article has a two-fold aim. The first aim is to reach the experiences and voiced concerns of precarious and vulnerable migrants to those who may be in a position to ameliorate their distress. Since policy-makers tend to lack time, findings from the qualitative data have been summarized in the form of a multi-dimensional typology, open to expansion by further research. The typology sees themes in money, health, information, and isolation. Second, the article follows the issues in the typology to suggest that acknowledgment of the significant role of migrant workers in India's economy, via sensitive enumeration, would be a first, and essential step to address the multiple concerns raised by migrant workers themselves. This baseline information could then be used to build subsequent dependent steps addressing the myriad causes of mental health distress among migrant workers in India.